(untitled) (Communications in Computational Physics, 2019)
We consider a midpoint scheme to approximate analytical solutions to a white noise driven BBM equation that reads du−duxx+ux ◦dW+upuxdt=0. We prove the well-posedness of the time-discrete approximation scheme and we provide the strong error order, which is 1.